(untitled) (Cadernos de Sociomuseologia, 2010)
Using this metaphoric framework as a starting point, I would like to focus on the characteristics of the District Six Museum which extend its work beyond being that of representation (of traumatic memory). Representation signifies in some ways distance and separation, a telling of a story depicted for others. The work of the Museum is more akin to what could broadly speaking be described as ‘engagement’. Although this is word is much over-used, it nonetheless indicates more closely an embodied practice which invites personal insertion, empathy and emplacement. It includes a whole range of sense-making practices by those closest to the Museum’s story – the dispossessed ex-residents – who participate in the memorialisation practices of the Museum in both harmonious and dissonant ways. The architectural metaphor of this seminar is key to this approach, indicating a practice which is constructed and layered, fixed yet changeable. It speaks to a spectrum of activities related to the imperatives to develop as well as conserve – elements which are central to the Museum’s work in relation to the process of return and restitution. To signify the unfinished business of representation, the permanent exhibition is called Digging Deeper, a framework which allows for an always further uncovering of facts, meanings and perspectives.